Single Tri-Epitopic Antibodies (TeAbs) to Botulinum Neurotoxin Serotypes B, E, and F Recapitulate the Full Potency of a Combination of Three Monoclonal Antibodies in Toxin Neutralization - Jianlong Lou; Wei Hua Wen; Fraser Conrad; Christina C. Tam; Consuelo Garcia-Rodriguez; Shauna Farr-Jones; James D. Marks (Toxins)
Recombinant monoclonal antibody (mAb) botulinum neurotoxin (BoNT) antitoxins, consisting of three mAbs that bind non-overlapping epitopes, are highly potent. However, the three-mAb mixtures pose unique development and manufacturing challenges. Combining even more mAbs to create multivalent antitoxin drugs multiplies those challenges. We previously reported that a single tri-epitopic IgG1-based mAb (TeAb) containing the variable domains of the three parental BoNT/A mAbs and an Fc was as potent as the combination of three IgGs in the mouse neutralization assay (MNA). Here, we extended the tri-epitopic strategy to three other BoNT serotypes. Each TeAb (TeAb-B for BoNT/B, TeAb-E for BoNT/E, and TeAb-F for BoNT/F) binding was measured using fluorescence-activated cell sorting and flow fluorimetry, and the potency was tested in the MNA. The three TeAbs displayed binding affinities that were the same within error of the parental IgGs for each epitope, and all had higher avidity to each serotype of BoNT than that of the parental mAbs. The potency of the BoNT/B, BoNT/E, and BoNT/F TeAbs was similar to the combinations of the three parental IgGs binding BoNT/B, BoNT/E, and BoNT/F in the MNA. We now have four examples of a single TeAb recapitulating the affinity and in vivo potency of a three-mAb antitoxin. The tri-epitopic strategy could be applied to streamline the production and bioanalytics of antibody drugs where three-mAb binding is required for activity.